The Role of Teachers and Parents in Building Ethical Values for The Formation of Students Character - kurniawan, Adi; Utami, Ratnasari Diah (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2024)
The role that educators and parents play in shaping a childs character is inextricably linked to the curriculum, as well as to the moral and personal principles that are instilled in them from a young age through habit and modeling. Character education cannot function in harmony with the goal of developing pupils with character without cooperation between the two. The purpose of this study is to (1) ascertain how parents and instructors influence students character development. (2) elements that help and hinder students from developing their character; (3) the process by which students develop their character. This study is qualitative and descriptive in nature. Parents, kids, and teachers were the sources of the data. Data was gathered by observation, documentation, technique and source training-assisted data validity testing, interviews, and observation. After that, an interactive model that comprises data reduction, data presentation, and conclusions is used to examine the data. The studys findings demonstrate the following: (1) the importance of parents and educators in serving as positive role models for kids conduct and personalities, including independence, teamwork, global variety, creativity, and a strong sense of faith and devotion to God Almighty. The school communitys dedication, the principals leadership, and parents participation in school activities are all supportive aspects. Apathy, certain parents and instructors parenting philosophies, and parents ignorance of character education are impediments, on the other hand. (3) The supervision and refraction approach is the most effective strategy to mold pupils character.